Glioblastoma treatment with hypofractionated radiotherapy versus conventional radiotherapy in patients older than 60 years - Müller, Maria Claro (2023)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2023